Visible Light Assisted Radical‐Polar/Polar‐Radical Crossover Reactions in Organic Synthesis - Sharma, Shivani; Singh, Jitender; Sharma, Anuj (Advanced synthesis & catalysis, 2021)
Chemists are generally familiar with polar reactions and radical reactions, in comparison, are underdeveloped. In the last few years, however, the novel concept of amalgamation of the above two in the form of radical‐polar crossover (RPCO) and polar‐radical crossover (PRCO) reactions has emerged as a valuable and powerful tool. This methodology tends to bridge the gap between the two as well as overcomes limitations of both radical and traditional polar chemistry. By bringing together the unorthodox chemistry of radicals with orthodox carbocations and carbanions, the green quotient of such reactions is significantly improved. The development and shaping up of this area in the last few years in the form of synthetically important transformations is summarised in this review.